Design of masonry buildings of three‐layered units according to Eurocode 6 / Bemessung von Mauerwerksbauten aus Dreischichtsteinen nach Eurocode 6. Issue 3 (June 2015) - Loderer, Franz
Abstract In the recent past, the masonry industry has developed many different solutions for optimising the heat protection of buildings. This took place for the building materials, geometric design, but also by development of multiple layered stones in which the components masonry unit, insulation and outer shell have been integrated into a block.